2012
DOI: 10.2147/dhps.s28804
|View full text |Cite
|
Sign up to set email alerts
|

Clinical use of antidepressant therapy and associated cardiovascular risk

Abstract: A number of different psychotropic agents have been associated with an increased risk of cardiovascular disease, and these relationships have been difficult to interpret due to the presence of confounding factors. Recently, there has been renewed interest in the potential for certain antidepressants to cause QT prolongation, which is a predisposing factor for arrhythmia. However, the optimum means of determining QT remains contentious due to discrepancies between methods that may be readily applied in a clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 81 publications
0
39
0
2
Order By: Relevance
“…A final limitation is that we did not obtain data regarding antidepressant use from this cohort. Thus, we cannot determine whether the use of antidepressants with known adverse cardiovascular effects, such as tricyclic antidepressants (34), is partially responsible for the observed relationship between depressive symptoms and incident CAD events.…”
Section: Discussionmentioning
confidence: 99%
“…A final limitation is that we did not obtain data regarding antidepressant use from this cohort. Thus, we cannot determine whether the use of antidepressants with known adverse cardiovascular effects, such as tricyclic antidepressants (34), is partially responsible for the observed relationship between depressive symptoms and incident CAD events.…”
Section: Discussionmentioning
confidence: 99%
“…In those patients who do demonstrate improvements in depressive symptoms with antidepressant therapies, a time-lag in the onset of therapeutic effects is frequently reported. Antidepressant drugs are associated with adverse side effects (Agency for Health Research and Quality (AHRQ), 2012) and an increased risk of cardiovascular disease, particularly in those with pre-existing cardiovascular conditions or major cardiovascular risk factors (Waring, 2012). Furthermore, adherence to antidepressant medications is often poor and patients often prematurely discontinue their antidepressant therapy; it has been suggested that approximately 50% of psychiatric patients and 50% of primary care patients are non-adherent when assessed 6-months after the initiation of treatment (Sansone and Sansone, 2012).…”
mentioning
confidence: 99%
“…It has been, however, reported that citalopram may lead to cardiovascular risk, for example QT prolongation, within the clinical concentration range (26), whereas the relation between Kv1.5 inhibition and QT prolongation is not completely clear. The IC 50 value of citalopram for Kv1.5 obtained by the post-ES viability assay (1.5 mM) was comparable to that determined electrophysiologically in the precedent study (2.8 mM) (17) but slightly lower than that obtained electrophysiologically in this study (at the pulse end: 7.48 mM).…”
Section: Discussionmentioning
confidence: 98%